Pengaruh Kesehatan dan Keselamatan Kerja Terhadap Kinerja Karyawan Dengan Keterampilan Sebagai Variabel Mediator - Haliza Mutiasari Jailani; Vera Anitra; Achmad Efendi (eCo-Buss, 2025)
This study aims to analyze the influence of occupational health and safety (OHS) on employee performance, with skills as a mediating variable at PT. Sumber Bara Abadi. A quantitative approach was applied using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The entire population of 70 permanent employees was used as the sample through a saturated sampling technique. Data were collected through questionnaires and analyzed using SmartPLS. The results showed that OHS significantly affects skills (coefficient = 0.462; P-value = 0.002) and significantly affects employee performance (coefficient = 0.461; P-value = 0.000). Additionally, skills significantly influence performance (coefficient = 0.273; P-value = 0.026). However, the moderating effect of skills on the relationship between OHS and performance was not significant (P-value = 0.284). The R² value indicates that the independent variables explain 21.3% of the variance in skills and 56.2% of the variance in performance. The Q² value of 0.273 indicates a moderate predictive relevance of the model for performance. These findings suggest that OHS and skills are critical factors in improving performance, with skills functioning more effectively as a mediating variable than as a moderator. The study implies that companies should continuously invest in both OHS programs and skill development to foster a safe, productive, and sustainable work environment.